STATE AND RELIGION IN MALAYSIA: CONSTITUTIONAL FOUNDATIONS AND SOCIAL PRACTICE (The Journal of Interdisciplinary Human Studies, 2026)
This article examines Malaysia’s religious landscape as a multi-ethnic and multi-confessional society and analyzes the state’s religious policy from legal, institutional, and social perspectives. The study highlights the structure of Malaysia’s religious education system, the activities of both state and private religious institutions, and the role of the International Islamic University Malaysia (IIUM) in the sphere of international Islamic education. In addition, the article explores social challenges emerging in the context of ethnic and religious diversity, ideological differences among political parties, and the key features of Malaysia’s state policy against extremism and terrorism. Based on the findings, the article presents scholarly conclusions regarding the significance of Malaysia’s experience in preventing the spread of Islamophobia.
Keywords: Malaysia; religious policy; religious tolerance; Islam; Shafi‘i school; interfaith relations; Islamic law; social stability; religious education